The Concept of War (Qitāl) in the Qur’an: A Comparative Study of Tafsir Al-Mishbah and Tafsir Al-Muharrar Al-Wajiz - Rochmad Rochmad; Muhammad Izzudin; Wahyu Septrianto; Radwan Jamal Yousef Elatrash; Ahmad Syaifullah (Universitas Darussalam Gontor, 2026)
The study of war or qitāl in the Qur'an often causes controversy, primarily because some circles still associate verses of jihad with violence or terrorism. This indicates a gap in understanding that needs to be bridged through in-depth tafsir (exegesis) studies. This research aims to analyze the concept of war in the Qur'an through a comparative study of two tafsirs: Tafsir Al-Mishbah by Quraish Shihab and Tafsir Al-Muharrar Al-Wajiz by Ibn Athiyyah. The method used is qualitative research based on a literature study with a thematic and comparative approach. The results show that both mufassirs (exegetes) agree that war in Islam is defensive in nature, oriented toward justice, and limited by humanitarian values. War is not intended as a means of aggression but as a last resort for self-defense and the protection of religious freedom. However, differences are observed in the emphasis: Tafsir Al-Mishbah highlights the contextual, moral, and spiritual aspects more, while Tafsir Al-Muharrar Al-Wajiz tends to emphasize the legal side of fiqh (Islamic jurisprudence) and linguistic debates. This study contributes by demonstrating how contextual-moral and fiqh-linguistic approaches complement each other in constructing a holistic Qur’anic understanding of war.